A prospective randomized feasibility trial comparing angiography and angiography with intravascular ultrasound for treatment of hemodialysis access failures. (August 2022) - Shutze, William; Rendon, Rachel; Lee, Victoria; Hu, Minyi; Duffy, Áine; Adelman, Mark
Objective: Hemodialysis accesses suffer from limited primary patency requiring frequent interventions, revisions, or even abandonment. Prolongation of access life and usability with minimization of these adverse events is paramount. Endovascular methods are established first-line interventions for failing arteriovenous access and treatment of venous outflow stenoses. The Primary goal of this feasibility study was to evaluate intravascular ultrasound (IVUS) during interventional treatments on outcomes in those undergoing angiography for failing hemodialysis access. Secondary goals were to determine differences between IVUS and angiography on vessel and lesion characteristics and impact on treatment. Methods: In this prospective, randomized controlled trial, patients scheduled for angiography to evaluate and treat a failing hemodialysis access were randomized to use of angiography (DSA) alone or angiography plus IVUS (DSA + IVUS). Patients were treated by a standardized protocol and seen in follow-up at 2 weeks, and every 3 months for 2 years or until a study endpoint was reached. Measurement of vessel diameters, % stenosis, lesion length, and study endpoints (AV access thrombosis, re-intervention, or surgical revision) were recorded. Results: A total of 55 subjects were enrolled, 27 in the DSA cohort and 28 in the DSA + IVUS cohort. There were 41 treated lesions in each group. Freedom from the composite endpoint of AV access thrombosis or re-intervention was 46.3% in the DSA cohort and 61.0% in the DSA + IVUS cohort ( p = 0.27). Diameter measurements matched between the two imaging modalities only 9 times out of 41 total comparison measures. In pre-treatment lesions with >80% stenosis, IVUS had a greater tendency than DSA to underestimate the severity of stenosis, whereas in pre-treatment lesions with 50–80% stenosis, DSA was more likely than IVUS to underestimate the severity of stenosis. Post-treatment % stenosis had mean difference of −7.5% between DSA versus DSA + IVUS cohorts. In five lesions with <30% stenosis measured by angiogram, IVUS led to treatment escalation. Conclusion: In the interventional treatment of failing angioaccess, IVUS and angiography differ in the vast majority of cases in measurement of vessel diameter. A significant number of patients were found to have suboptimal therapeutic response by IVUS only, which led to an escalation in treatment, and in over one-third of cases, the IVUS results led to a change in treatment plan. The improved patency rates in the IVUS group was not statistically significant in this small population but should be further investigated in a larger trial.